Metabolic reprogramming enables hepatocarcinoma cells to efficiently adapt and survive to a nutrient-restricted microenvironment. Issue 7 (3rd April 2018) - Cassim, Shamir; Raymond, Valérie-Ann; Dehbidi-Assadzadeh, Layla; Lapierre, Pascal; Bilodeau, Marc
ABSTRACT: Hepatocellular carcinoma (HCC) is a metabolically heterogeneous cancer and the use of glucose by HCC cells could impact their tumorigenicity. Dt81Hepa1-6 cells display enhanced tumorigenicity compared to parental Hepa1-6 cells. This increased tumorigenicity could be explained by a metabolic adaptation to more restrictive microenvironments. When cultured at high glucose concentrations, Dt81Hepa1-6 displayed an increased ability to uptake glucose ( P <0.001), increased expression of 9 glycolytic genes, greater GTP and ATP ( P <0.001), increased expression of 7 fatty acid synthesis-related genes ( P <0.01) and higher levels of Acetyl-CoA, Citrate and Malonyl-CoA ( P <0.05). Under glucose-restricted conditions, Dt81Hepa1-6 used their stored fatty acids with increased expression of fatty acid oxidation-related genes ( P <0.01), decreased triglyceride content ( P <0.05) and higher levels of GTP and ATP ( P <0.01) leading to improved proliferation ( P <0.05). Inhibition of lactate dehydrogenase and aerobic glycolysis with sodium oxamate led to decreased expression of glycolytic genes, reduced lactate, GTP and ATP levels ( P <0.01), increased cell doubling time ( P <0.001) and reduced fatty acid synthesis. When combined with cisplatin, this inhibition led to lower cell viability and proliferation ( P <0.05). This metabolic-induced tumorigenicity was also reflected in human Huh7 cells by a higher glucose uptake and proliferative capacity compared to HepG2 cells ( P <0.05). In HCC patients, increased tumoral expression of Glut-1, Hexokinase II and Lactate dehydrogenase correlated with poor survival ( P = 2.47E −5, P = 0.016 and P = 6.58E −5 ). In conclusion, HCC tumorigenicity can stem from a metabolic plasticity allowing them to thrive in a broader range of glucose concentrations. In HCC, combining glycolytic inhibitors with conventional chemotherapy could lead to improved treatment efficacy.